Critical Success Factors for Open Government Data Management Information Systems in a Public Body in the State of São Paulo - Gonçalves, Vagner Mendonça; Araujo, José Braz de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2023)
Context: In Brazil, access to public government data and information is a citizen's right and at the same time a means of overseeing and auditing the government actions. Thus emerges the challenge for municipal, state and federal governments to provide effective means that allow public government data and information to be, in fact, accessible (open) to Brazilian citizens in an understandable and usable way for the most different purposes. In this context, Information Technology is a key area to building management and governance Information Systems for the immense amount of data and information generated by the Public Administration. Problem: Identify and analyze the critical success factors for the planning, implementation and application of effective Information Systems aimed at the management of Open Government Data, transparency and access to information in a Public Body in the State of São Paulo (SP). Solution: Through a case study, we have analysed how a public body in SP has been acting for the planning, implementation and continuous improvement of its processes and Information Systems in order to evolve in terms of transparency and Open Government Data management. IS Theory: Theory of Critical Success Factors. Methods: In general, a theoretical-empirical research was carried out which, from the point of view of technical procedures, can be considered as a case study that used the techniques of document analysis and participatory observation. Summary of Results: A list of practices that can be adopted by public bodies in SP in order to increase the effectiveness of their actions aimed at building Information Systems that facilitate access to information and promote transparency. Contributions and Impact in the IS area: The results are able to guide initiatives of automation and improvements in organizational processes of public bodies in SP aimed at the described purpose.